2022
DOI: 10.1055/s-0040-1719870
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of Isoquinoline Derivatives through Sequential Cyclization–Deoxygenation Reaction of 2-Alkynylbenzaldoximes

Abstract: We describe a novel, simple, robust, and efficient cyclization/deoxygenation approach for the synthesis of functionalized isoquinoline derivatives. Over the course of continued studies on o-alkynylbenzaldoxime cyclization reactions, the formation of cyclic nitrones through 6-endo-dig cyclization was achieved using silver triflate or bromine as an electrophile, and subsequently, the deoxygenation process was carried out in the presence of CS2 in good to high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Ayoubi et al reported a one-step synthesis of 3-substituted isoquinoline scaffolds 378a and 378b (Scheme 76). 122 Iminol scaffold 375 delivers its corresponding N -oxide intermediate 376 on reaction with AgOTf/Br 2 . Cycloaddition of the intermediate 376 with CS 2 generates the oxathiazolidine intermediate 377 .…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
“…Ayoubi et al reported a one-step synthesis of 3-substituted isoquinoline scaffolds 378a and 378b (Scheme 76). 122 Iminol scaffold 375 delivers its corresponding N -oxide intermediate 376 on reaction with AgOTf/Br 2 . Cycloaddition of the intermediate 376 with CS 2 generates the oxathiazolidine intermediate 377 .…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%